The Antimicrobial Effect of Pomegranate Peel Extract versus Chlorhexidine in High Caries Risk Individuals Using Quantitative Real-Time Polymerase Chain Reaction: A Randomized Triple-Blind Controlled Clinical Trial - Benoy Jacob; Nivedhitha Malli Sureshbabu; Manish Ranjan; Aishwarya Ranganath; Riluwan Siddique (International Journal of Dentistry)
The aim of the present study was to compare the antibacterial effectiveness of chlorhexidine and PPE oral rinse on S. mutans, Lactobacilli, and Veillonella, in clinical salivary samples of patients with advanced stages of dental caries at baseline and two and four weeks with PCR technique. This triple-blind randomized clinical trial involved 60 high caries risk adult patients, 19–59 years of age, randomly allocated into two groups of 30 subjects each. The intervention group received pomegranate peel extract mouthwash, whereas the control group received chlorhexidine mouthwash. Unstimulated pooled saliva was collected from the floor of the mouth before and after the intervention. The quantitative real-time polymerase chain reaction was employed to analyze the bacterial copies of each salivary sample at baseline and two and four weeks. The significance level was fixed at 5% (α = 0.05). Overall comparison of antimicrobial effectiveness across both groups revealed insignificant outcomes. The control group evinced a significant reduction in S. mutans between a specific time, i.e., baseline and 4 weeks (p=0.043). PPE oral rinse as a natural product or ecological alternative was effective in disrupting activity across all microorganisms tested in this triple-blind RCT; however, the nutraceutical, when compared to chlorhexidine, was not as effective against S. mutans.